18F-FDG PET/CT in Pulmonary Sarcoidosis:Quantifying Inflammation by the TLG index. (2nd January 2020) - Papiris, Spyros A; Manali, Effrosyni D; Pianou, Nikoletta K; Kallergi, Maria; Papaioannou, Andriana I; Georgakopoulos, Alexandros; Malagari, Katerina; Kelekis, Nikolaos L; Gialafos, Helias; Chatziioannou, Sofia
ABSTRACT: Objectives : In sarcoidosis progressive pulmonary disease affects prognosis. Pulmonary disease activity estimated by classic means poorly predicts severity and progressiveness. 18 F-fluoro-2-deoxyglucose-positron-emission-tomography computed-tomography ( 18 F-FDG-PET/CT) estimates pulmonary activity by inflammatory-cells metabolism. We aimed to investigate pulmonary sarcoidosis by 18 F-FDG-PET/CT and evaluate the role of total-lesion-glycolysis (TLG) value, as an index quantifying the whole burden of lung inflammation. Methods : This is a retrospective study of sequentially gathered data. From a Greek cohort of 195 sarcoidosis-patients, 87 were identified with lung increased 18 F-FDG uptake and further studied. Results : Visualizing lung by 18 F-FDG-PET/CT identified new imaging patterns and revealed activity in all Scadding stages. Ever-smokers presented significantly higher TLG and lower DLCO compared to never-smokers. However, TLG value did not correlate with functional indices and did not differ between symptomatic and non-symptomatic patients. Among treatment-naïve patients, TLG did not differ significantly in those requiring therapy compared to those remained off. Conclusion : 18 F-FDG PET/CT improved imaging and detection of pulmonary involvement and through TLG value revealed the deleterious smoking effect. The fact that TLG neither detected patients with clinical symptoms and functional impairment nor identified those requiring treatment once again confirms that in pulmonary sarcoidosis the link between activity, severity and decision to treat still eludes us.